Development of Somatic Embryo Maturation and Growing Techniques of Norway Spruce Emblings towards Large-Scale Field Testing - Mikko Tikkinen (Forests, 2018)
The possibility to utilize non-additive genetic gain in planting stock has increased the interest towards vegetative propagation. In Finland, the increased planting of Norway spruce combined with fluctuant seed yields has resulted in shortages of improved regeneration material. Somatic embryogenesis is an attractive method to rapidly facilitate breeding results, not in the least, because juvenile propagation material can be cryostored for decades. Further development of technology for the somatic embryogenesis of Norway spruce is essential, as the high cost of somatic embryo plants (emblings) limits deployment. We examined the effects of maturation media varying in abscisic acid (20, 30 or 60 µM) and polyethylene glycol 4000 (PEG) concentrations, as well as the effect of cryopreservation cycles on embryo production, and the effects of two growing techniques on embling survival and growth. Embryo production and nursery performance of 712 genotypes from 12 full-sib families were evaluated. Most embryos per gram of fresh embryogenic mass (296 ± 31) were obtained by using 30 µM abscisic acid without PEG in the maturation media. Transplanting the emblings into nursery after one-week in vitro germination resulted in 77% survival and the tallest emblings after the first growing season. Genotypes with good production properties were found in all families.